Co-Digestion of Cattle Slurry and Food Waste: Perspectives on Scale-Up - Angela Bywater; Jethro A. H. Adam; Sigrid Kusch-Brandt; Sonia Heaven (Methane)
Anaerobic digesters fed with dairy cow slurry struggle to achieve economic viability, particularly when animals are housed seasonally, so additional feedstocks are usually required. This study applied experimentally derived data from the co-digestion of cow slurry (CS) and food waste (FW) to the UK dairy herd as a whole, and at average (AH) and large (LH) herd sizes of 160 and 770 animals, respectively. The experimental data confirmed stable operation at an organic loading rate (OLR) of 5 g VS L−1 day−1 at CS:FW ratios of 3:1 and 6:1 on a wet weight basis, and these parameters were considered for both AH and LH by herd size and country (Scotland, England, Wales, Northern Ireland) in order to provide energy production and policy observations. The results showed that these scenarios could provide between 959 to 23,867 GJ per year, and that a targeted policy intervention could affect slurry treatment from a significant number of animals in a relatively small number of large herds across the UK. For a more detailed analysis, better data are required on non-domestic FW arisings and FW transportation needs.